Multimedia Teacher Research - Heather Leaman; Connie DiLucchio (Networks: An Online Journal for Teacher Research, 2015)
In this qualitative study, two teacher educators and course instructors in a Masters of Education (M.Ed.) program explored beginning teacher researchers’ use of multimedia to support action research. Fifty-eight teachers (36 in spring 2010 and 22 in spring 2011) completed teacher research as the capstone in their M.Ed. program. Teachers utilized the MERLOT website (Multimedia Educational Resource for Learning and Online Teaching) to develop and submit their research as an alternative to traditional paper submission. As teachers conducted their research, course instructors investigated how the teachers’ use of multimedia strengthened or limited their teacher research work. Data from teacher researchers (questionnaires, observations and reviews of final projects) were analyzed for emergent themes. All teacher participants were able to use multimedia successfully in their teacher research projects. Technology difficulties were few, and findings suggest that multimedia options encouraged the use and development of technological skills, increased time teachers spend editing and revising work, and facilitated organization of the research process. The authors conclude that traditional paper submissions may be replaced by a multimedia format without detracting from the teacher research project and may serve to enhance the action research process.